2016
DOI: 10.5812/jjm.29766
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Evaluation of Blood Culture Practices, Contamination Rates, and the Distribution of Causative Bacteria

Abstract: Background:The prognostic value of blood culture testing in the diagnosis of bacteremia is limited by contamination.Objectives:In this multicenter study, the aim was to evaluate the contamination rates of blood cultures as well as the parameters that affect the culture results.Materials and Methods:Sample collection practices and culture data obtained from 16 university/research hospitals were retrospectively evaluated. A total of 214,340 blood samples from 43,254 patients admitted to the centers in 2013 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…When working pre‐hospitally in less than optimal conditions, it is often easiest to draw BCs from the peripheral venous catheter as this is being inserted. This, however, has proven to be associated with higher contamination rates 27 …”
Section: Discussionmentioning
confidence: 99%
“…When working pre‐hospitally in less than optimal conditions, it is often easiest to draw BCs from the peripheral venous catheter as this is being inserted. This, however, has proven to be associated with higher contamination rates 27 …”
Section: Discussionmentioning
confidence: 99%
“…Another measure to decrease contamination is to disinfect the blood culture bottle septum with 70% isopropyl alcohol or ethanol before injecting the blood sample (88, 193, 229, 230); in many institutes, however, this is not done routinely (193, 231). Bekeris et al did not find evidence for the effectiveness of this measure in decreasing contamination, however they noted that their study was not powered to detect such an effect as they had quite low rates of contamination overall (206).…”
Section: Methods and Techniques For Processing Manual Blood Culturesmentioning
confidence: 99%
“…Furthermore, we must emphasize the possible loss of 10/298 cases of candidemia and six cases of MRSA bacteraemia because of the high morbidity and mortality of these infections [21e24]. Prior studies have reported contamination rates of less than 3% of positive blood cultures, in which CoNS was the most frequent microorganism (44.0%) [25,26].…”
Section: Discussionmentioning
confidence: 99%